Application of Constructivism Approach to Improve the Quality of Learning Geography - Frist Adam Tampubolon; Yurni Suasti (Postgraduate School, Universitas Negeri Padang, 2020)
The constructivism approach is one approach in learning that is appropriate to encourage participation, activity and creativity, and independence of students in learning activities. This is supported by the concepts and understandings contained in the underlying theory. The constructivist approach focuses on how students build and discover their knowledge so that learning will be more interesting. Geography is a science that studies the phenomenon of the geosphere that is spread over the earth's surface with its diversity. Learning geography will be more interesting if it is carried out with a constructivist approach, because in learning students are not passive objects, but will be encouraged to be active, and creative, build their knowledge and be able to apply the information they have in understanding, analyzing and solving problems of geographical phenomena themselves. The application of the Constructivism approach in geography learning can improve the quality of geography learning. This can be seen through interactive learning with two-way communication, the level of participation of students involved in learning is getting higher, the learning motivation of students is getting higher, the ability of students to understand concepts is getting better, and the ability of students to solve geographical problems is also getting better.